Psikoedukasi Anti Bullying pada Remaja di Pondok Pesantren Nurul Yaqin - Vatin, Nurva Dillatul; Yanti, Novi; Syamsurizal, Syamsurizal; Sitorus, Ismawati; indra wandi, Joni (Institut Agama Islam Sumatera Barat, 2024)
The phenomenon of bullying among adolescents has shown a significant increase and negatively impacts their health. This study aims to evaluate the effectiveness of an anti-bullying psychoeducational program in reducing bullying behaviors and enhancing adolescents' awareness and knowledge about the negative effects of bullying. The research utilizes a non-experimental quantitative approach involving a psychoeducational intervention specifically designed for adolescents. The participants in this study were 310 adolescents from Nurul Yaqin Islamic Boarding School. The program includes training sessions, group discussions, and interactive activities aimed at strengthening empathy, communication skills, and bullying prevention strategies. The results of the study indicate that participation in the psychoeducational program significantly reduced the frequency of bullying behaviors and improved adolescents' understanding of the importance of combating bullying. The implications of this research suggest that implementing anti-bullying psychoeducation can be an effective strategy in creating a safer and more supportive environment in Islamic boarding schools for adolescents.